Verkündigung und Forschung (Gütersloher Verlagshaus, 1940)
The review journal Verkündigung und Forschung features collective reviews of publications from the individual theological disciplines. Each issue focuses on a specific topic chosen from the respective discipline. Additionally, there are thematic reviews supplementing the focal point from the perspective of cognate disciplines or commenting on current developments in church, school, and society.The reviews are each written with a special focus. They provide readers with a thematic survey and encourage the forming of own opinions at a time. For academic studies: Focusing on specific research topics within the individual theological disciplines, Verkündigung und Forschung is a valuable tool for the strategic compilation of final examination themes. Although this cannot substitute the reading of the referenced titles, it facilitates thematic orientation and selective choice of literature. For religious education teachers: Teachers often lack the time for an in-depth exploration of a topic. Verkündigung und Forschung stimulates well-grounded religious education through its concise surveys of a central topic which is - although focused on theology - additionally accessed from the perspective of cognate disciplines. For pastors: Many practitioners regret losing the contact to scholarly discussions of theological topics due to their daily work load. The concise reviews in Verkündigung und Forschung help to re-establish this contact and provides impulses for critical access. ---------- PRINT available from Gütersloher Verlagshaus:http://www.fachzeitschriften-religion.de/verkuendigung-un